Odpowiedzi

2010-03-09T21:24:35+01:00
-3x=2x-10
-5x=-10/:-5
x=2

2x-2=7-x
3x=9/:3
x=3

10=4-2x
6=-2x/:-2
x=-3

-(2x-1)=4
-2x+1=4
-2x=3/:-2
x=-1,5

2(x+1)=x
2x+2=x
x=-2

2t-(3t+1)=6
2t-3t-1=6
-t=7/:-1
t=-7

-(4+x)=2(3-x)
-4-x=6-2x
x=10

3(y+6)-y=2(y+9)
3y+18-y=2y+18
0=0

(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x=20/:-5
x=-4
2010-03-09T21:28:00+01:00
-3x=2x-10 / -2x
-5x=-10 / :(-5)
x=2

2x-2=7-x / +x +2
3x=9 / :3
x=3

10=4-2x / -4
6=-2x / :(-2)
x=-3

-(2x-1)=4 / *(-1)
2x-1=-4 / +1
2x=-3 / :2
x= -3/2 (minus trzy drugie)

2(x+1)=x
2x +2=x / -2x
-x=2
x=-2

2t-(3t+1)=6
2t-3t-1=6 / +1
-t=7
t=-7

-(4+x)=2(3-x)
-4-x=6-2x / +x -6
-10=-x
x=10

3(y+6)-y=2(y+9)
3y+18-y=2y+18 / -18
2y=2y
L=P (lewa strona równa się prawej)
x∈R (x należy do rzeczywistych)

(x-7)-2(3x+5)=3
x-7-6x-10=3
-5x-17=3 / +17
-5x=20 / :(-5)
x=-4